Asertividad comunicacional en la integración de las funciones sustantivas de la Universidad Particular de Loja Campus Quevedo, Provincia de Los Ríos, año 2019 - Tene Manguia, Johny David (2020)
Communication assertiveness is fundamental in the teaching-learning process due to the varied information and communication that is projected through behavior, because in many occasions there are difficulties to express themselves since there is no intention of working properly and in a group, rather you project bad ideas, many may not be objective in being able to express what they feel, but being assertive is having the sincerity of improving your behavior not offending anyone but being able to strengthen your friendship, although people are not convinced that assertiveness is a tool that It allows optimizing human relations, since it is not only saying what you think but also focusing on positive attitudes that do not affect anyone's susceptibility rather increasing the teaching process the human being always wants to be demanded, to fully comply in any scope in the labor, educational, business, social. But when the communication methods are not used appropriately, if the exchange of ideas is desired, it is not going to be possible and it becomes difficult to understand. It is there where honesty is being lost, but as in any institution there are conflicts, stereotypes, work problems, then you have to take active and concrete actions, focusing on what you want and be as specific as possible so as not to hurt susceptibilities and more. either become an example to be followed by future generations. The substantive functions are embedded in the learning process. Teaching, research and extension are all closely related because within the framework of social development, every event that occurs at present forces the university campus of the Province of Los Ríos to pay attention to those who fail to professionalize and have the opportunity to demonstrate their attitude deepening with immediate responses to the problems that affect men's activity both at the community level and also in a higher social environment, including the teacher, becomes the bridge for knowledge to go from generation to generation and projection social, they are responsible for training professionals for service and solidarity, since the three functions are closely linked with nature.